Bibliometrics Analysis of Butyrophilins as Immune Regulators [1992–2019] and Implications for Cancer Prognosis - Wang, Yixi; Zhao, Na; Zhang, Xianwen; Li, Zhenhua; Liang, Zheng; Yang, Jinrong; Liu, Xingyu; Wu, Yangzhe; Chen, Kebing; Gao, Yunfei; Yin, Zhinan; Lin, Xuejia; et al. (Frontiers in Immunology, 2020)
The butyrophilins represent a unique family of immunoglobulin. They were considered to be involved in milk lactation after their discovery in 1981. With the development of research, an increasing number of researches revealed that butyrophilins play important roles in immune regulation [1992-2019]. Our research aimed to summarize the butyrophilin research status and their relationship with lung cancers and breast cancers by bibliometric and bioinformatic methods. Our results indicate that the researches on immune-regulatory functions of butyrophilins gradually developed from 1992 to 2006, whereas increased quickly after 2007. There are international co-operations among 56 countries, of which the United States is the most active one with the largest number of studies as well as highest citations. By co-authorship and co-citation analysis, we showed that Adrian Hayday, who is active in γδ T cell field, was an active author in butyrophilin publications with average year of 2015 and led a sub-field. By keywords co-occurrence analysis, we found γδ T cell, which is an important cancer immune regulator, is one important hotspot. Finally, we found several butyrophilin members’ expression levels were significantly correlated with prognosis of lung cancer and breast cancer patients. Thus, these butyrophilins might play immune regulatory effects and could serve as potential biomarkers for cancer.